Invasive aspergillosis in an immunocompetent patient with fever and a cardiac mass - Matthew LaBarbera; Lester B. Jacobson (MDPI AG, 2011)
Invasive aspergillosis is an often fatal disease that usually occurs in immunocompromised patients. We report a case of invasive aspergillosis presenting as a febrile respiratory infection with a cardiac mass in an immunocompetent patient. Invasive aspergillosis should be considered in the differential diagnosis of an otherwise undiagnosed febrile respiratory illness, even in immunocompetent patients. Echocardiography should be peformed to evaluate for endocarditis in such cases. Prompt initiation of appropriate antifungal therapy is warranted, even before the diagnosis of invasive aspergillosis is confirmed.